PENGARUH KUALITAS PRODUK, HARGA DAN BRAND IMAGE TERHADAP MINAT BELI KONSUMEN MOTOR MATIC YAMAHA - Pratama, Vicram Putra (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This study aims to determine the effect of product quality, price and brand image on consumer buying interest for Yamaha Matic Motorcycles (Case Study of Management Study Program Students, Faculty of Economics and Business Class of 2019, University of Muhammadiyah Bengkulu). This type of research is a type of quantitative descriptive research, the object of this research is students of management study program, Faculty of Economics and Business, Muhammadiyah University of Bengkulu, which is precisely located on Jl. Lieutenant Suprapto, Kec. Ratu Samban, Bengkulu City, Bengkulu. The sampling method uses a non probability technique, namely accidental sampling. The number of respondents in this study were 180 people. Methods of data collection using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely t test and f test. The results of this study can be concluded that the variable Product Quality has a positive effect on Consumer Purchase Interest, Price has a positive effect on Consumer Purchase Interest, Brand Image has a positive effect on Consumer Purchase Interest, and Product Quality, Price and Brand Image have a positive and significant effect on Consumer Buying Interest in Yamaha Matic Motors. Keywords: Product Quality, Price, Brand Image, Consumer Purchase Interest